Influence of music therapy to reduce anxiety during periodontal surgical procedures / Erni Noor ... [et al.] - Noor, Erni; Abdul Halim, A; Mohd Fadzilah, A; Mohd Said, S; Abdul Halim, R (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
To evaluate the influence of music in reducing patients’ anxiety during periodontal surgery. Methods: This is a clinical trial of involving fifteen patients undergoing periodontal surgery. Patients indicated for periodontal surgery were invited to participate in the study, and randomly assigned to music (n=8) or control (n=7) groups. Participants’ dental anxiety were determined using the Corah Dental Anxiety Scale (CDAS) before and after the surgery, while their blood pressure (BP) and heart rate (HR) were recorded at pre-, intra- and post-procedures. Paired t-test was used to compare the statistical significant difference between pre- and postprocedural anxiety for both groups. The participants of this study consist of 22 patients that underwent periodontal surgery procedures, with majority of the subjects (53.3%) were males (n=8) and the mean age was 50.8 (SD=13.21). The measurement of blood pressure increased in patients allocated in music group compared to control group were statistically significant with (p<0.05). Our study suggests that music may reduce patients’ anxiety while undergoing periodontal surgery. More details on the type and intensity of music may provide further value to the finding.